1990
DOI: 10.1002/hyp.3360040108
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of suspended sediment in the upper rhone river, switzerland, including the particulate forms of phosphorus

Abstract: Six stations along the Upper Rhone River above Lake Geneva were sampled by continuous flow centrifuge for recovery of suspended sediment. The samples were taken four times, once in 1982 and three times in 1983. In addition the mouth of the river was sampled in a like manner every two weeks during 1982 until August 1983. Samples were analysed for the major elements SO,, A1,0,, K,O, MgO, Na,O, CaO, and Fe,O,; for trace elements, Zn, Cu, Ni, Mn, and Cr; for Org. C and Kjeldahl N; and the forms of phosphorus bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 10 publications
(7 reference statements)
2
20
0
Order By: Relevance
“…The supernatant was mineralised for 45 min at 130°C after addition of K 2 S 2 O 8 solution (5%). The P concentration was performed by measuring the absorbance of the blue complex obtained after reduction of molybdophosphoric acid according to the method described by Murphy and Riley (1962), Harwood et al (1969) and Burrus et al (1990).…”
Section: Organic Matter (Om) Total Nitrogen (N) and Total Phosphoroumentioning
confidence: 99%
“…The supernatant was mineralised for 45 min at 130°C after addition of K 2 S 2 O 8 solution (5%). The P concentration was performed by measuring the absorbance of the blue complex obtained after reduction of molybdophosphoric acid according to the method described by Murphy and Riley (1962), Harwood et al (1969) and Burrus et al (1990).…”
Section: Organic Matter (Om) Total Nitrogen (N) and Total Phosphoroumentioning
confidence: 99%
“…Total nitrogen and ammonium concentrations in the sediments were measured by using the method of Kjeldhal (1883). Total phosphorus and its different forms were determined following the fractionation scheme of Williams et al (1976) as modified by Burrus et al (1990). Sediment characteristics were measured before and at the end of the experimentation.…”
Section: Sediment and Water Characterizationmentioning
confidence: 99%
“…It was also shown that a substantial amount of calcium-bound P was solubilized by the citrate dithionite bicarbonate (CDB) reagent of Williams (1971Williams ( , 1976, for which the strongly chelating citrate ion was responsible. The CDB extraction was omitted by Burrus et al (1990), but the name of the modified procedure was not changed and usually listed as a later version of the Williams scheme (Golterman, 1996;Ruban et al, 1999b;Hoyle, 2004). The reason for this change was the belief that P extracted by NaOH reflects the P available to algae.…”
Section: Williams Methodsmentioning
confidence: 99%
“…Total P (TP) and molybdate reactive P were measured in the pooled extracts and OP calculated from the difference (Williams et al, 1976). The extraction scheme of Williams as modified by Burrus et al (1990) is not completely sequential, involving two independent procedures. …”
Section: Williams Methodsmentioning
confidence: 99%
See 1 more Smart Citation